Beban Pencemaran, Kapasitas Asimilasi dan Status Pencemaran Estuari Banjir Kanal Barat, Kota Semarang, Jawa Tengah - Haeruddin, Haeruddin; Purnomo, Pujiono Wahyu; Febrianto, Sigit (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
West Banjir Kanal river is part of Garang Catchment Area which used as souce for drinking water communities of West Semarang District, Central Java. The high intensities used of area around Garang Catchment Area for agriculture, settlement and industry caused water polluted. This research conducted to evaluate wastewater pollution load, assimilative capacity and pollution state of west Banjir Kanal estuary. The research done by survey method with collected of water samples from 3 sampling point with 3 replication respectively. The result showed that pollution loading are 8,450E-6 - 3,236E-7 ton/year TSS, 5,622E-4 – 6,728E-6 ton/year nitrate and 0 – 3,049E-6 ton/year phosphat, which are exceeded assimilative capacity of estuary for TSS, nitrate and phosphate, that are caused water pollution. Water Quality Index is 51,94 and showed that West Banjir Kanal Estuary is very high polluted with TSS, nitrate and phosphate.